2020
DOI: 10.1016/j.ekir.2020.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Serum-Free Light-Chain Assays in CKD Patients

Abstract: Introduction: Quantification of serum-free light chains (FLCs) is important in the diagnosis and monitoring of paraprotein-related diseases. There are currently 2 FLC assays available: the Freelite assay (Binding Site) and the N Latex assay (Siemens). There is emerging evidence that these assays give different results, but it is not established how kidney dysfunction affects these assays differently.Methods: In this study, we measured and compared serum FLCs in patients with mild-to-moderate chronic kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…It is demonstrated that hemodialysis contributes to serum FLCs ( 30 ). Additionally, the different FLCs detection methods might be responsible for the inconsistent findings of Desjardins L and ours, as FLCs are different by Freelite assay and by N Latex assay ( 31 ). The non-synchronicity of the alterations between microbiome composition and CKD stage and between microbiome composition and FLC κ/λ indicate that the rate of loss in kidney function decline appear to be inconsistent with the alterations of gut microbiome and FLCs.…”
Section: Discussionmentioning
confidence: 82%
“…It is demonstrated that hemodialysis contributes to serum FLCs ( 30 ). Additionally, the different FLCs detection methods might be responsible for the inconsistent findings of Desjardins L and ours, as FLCs are different by Freelite assay and by N Latex assay ( 31 ). The non-synchronicity of the alterations between microbiome composition and CKD stage and between microbiome composition and FLC κ/λ indicate that the rate of loss in kidney function decline appear to be inconsistent with the alterations of gut microbiome and FLCs.…”
Section: Discussionmentioning
confidence: 82%
“…It has been confirmed by many researchers that the determination of ratio by the N-Latex method has nothing to do with renal function [ 22 ]. The latest research in 2020 showed that the FLC κ / λ obtained by the Freelite method was negatively correlated with eGFR, while N-Latex was positively correlated, but they were all within the reference range of healthy people [ 23 ]. Our research also confirmed this.…”
Section: Discussionmentioning
confidence: 99%
“…These findings can be encountered in patients with chronic kidney disease (CKD) or with monoclonal gammopathy of undetermined significance (MGUS). In patients with CKD, as the glomerular filtration rate (GFR) declines, the renal clearance of polyclonal FLC decreases and serum concentrations rise 8 . The FLC ratio also varies as the GFR declines, but this depends on the FLC assay available [Freelite assay (Binding Site, Birmingham, UK) or N Latex assay (Siemens, Marburg, Germany)] 8 .…”
Section: Definitions and Classificationsmentioning
confidence: 99%
“…In patients with CKD, as the glomerular filtration rate (GFR) declines, the renal clearance of polyclonal FLC decreases and serum concentrations rise 8 . The FLC ratio also varies as the GFR declines, but this depends on the FLC assay available [Freelite assay (Binding Site, Birmingham, UK) or N Latex assay (Siemens, Marburg, Germany)] 8 . With the N Latex assay, the FLC ratio decreases as GFR declines but no reference range in CKD has yet been proposed.…”
Section: Definitions and Classificationsmentioning
confidence: 99%
See 1 more Smart Citation